2019
DOI: 10.1159/000503859
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with Biologic Treatment in Patients with Inflammatory Bowel Disease: A German Claims Data Analysis

Abstract: Objectives: This study aimed to assess the real-world rates of treatment discontinuation and switching of biologic therapies in patients with inflammatory bowel disease (IBD). Methods: A retrospective claims data analysis on all continuously insured adult IBD patients with initiation of a biologic therapy was conducted. Observation started with the date of the first prescription of index tumor necrosis factor α-inhibitors (anti-TNFα) or vedolizumab (VDZ) therapy and lasted 12 months. Non-persistence was assume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
(27 reference statements)
2
12
1
1
Order By: Relevance
“…prescribing according to insurance agency contracts, co-payment costs, requirement to initiate treatment using biosimilars, or from single-centre study bias, which are limitations in other persistence studies. [13][14][15][16][17][18][19] Our study was the first to simultaneously report on the persistence of both ustekinumab and vedolizumab and found them to have significantly higher persistence than anti-TNF agents for luminal CD and moderate-to-severe UC respectively. In both luminal CD and moderate-severe UC, non-anti-TNF agents had highest persistence compared to anti-TNF agents.…”
Section: Factors Associated With Persistencementioning
confidence: 63%
See 3 more Smart Citations
“…prescribing according to insurance agency contracts, co-payment costs, requirement to initiate treatment using biosimilars, or from single-centre study bias, which are limitations in other persistence studies. [13][14][15][16][17][18][19] Our study was the first to simultaneously report on the persistence of both ustekinumab and vedolizumab and found them to have significantly higher persistence than anti-TNF agents for luminal CD and moderate-to-severe UC respectively. In both luminal CD and moderate-severe UC, non-anti-TNF agents had highest persistence compared to anti-TNF agents.…”
Section: Factors Associated With Persistencementioning
confidence: 63%
“…Vedolizumab improved persistence by 40% compared to anti‐TNF agents in moderate‐to‐severe UC. The 1‐year persistence of 73.4% compared with 64.0%‐69.7% previously reported but with smaller sample sizes and from an insurance database that might contain bias 13,16 . We hypothesise that the improved persistence of ustekinumab and vedolizumab vs anti‐TNF agents may be associated with reduced immunogenicity from their production using phage display transgenic technology, in contrast to the more immunogenic mouse chimeric or humanised structures of anti‐TNF agents 22 .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, HRU and direct costs after 36 months of follow-up were higher than the 24-month data, suggesting that some patients undergoing biologic treatment may not respond optimally after 24 months of treatment, and hence may have to switch treatment or undergo surgery to manage CD. This seems plausible since previous research has reported a reduction in persistence with biologics as time passes, with a wide range in the rate of non-persistence due to treatment discontinuation or switching [36][37][38][39].…”
Section: Plos Onementioning
confidence: 85%